Assessment of the Vanillin Anti-Inflammatory and Regenerative Potentials in Inflamed Primary Human Gingival Fibroblast - Erica Costantini; Bruna Sinjari; Katia Falasca; Marcella Reale; Sergio Caputi; Srinivas Jagarlapodii; Giovanna Murmura (Mediators of Inflammation)
Background. Inflammatory responses have been associated with delayed oral mucosal wound healing and the pathogenesis of the periodontal disease. The invasion of microbes into the tissues and the establishment of a chronic infection may be due to impaired healing. The protracted inflammatory phase may delay wound healing and probably support tissue fibrosis and reduce tissue regeneration. Vanillin is a well-known natural compound with potential anti-inflammatory capacity. Hence, we hypothesized that Vanillin could accelerate wound healing reducing inflammation and especially cytokine production making the oral tissue repair process easier. Methods. Our hypothesis was tested using primary human gingival fibroblast (HGF) cell pretreated with Vanillin and primed with IL-1β, as inductor of proinflammatory environment. After 24 hours of treatments, the gene expression and production of IL-6, TNF-α, IL-8, COX-2, iNOS, and nitric oxide (NO) generation and the wound healing rate were determined. Results. In IL-1β-primed cells, preincubation with Vanillin reduced IL-6, IL-8, COX-2, and iNOS expression and NO release, compared to IL-1β-primed cells. Moreover, Vanillin determines the increased gene expression of nAChRα7, leading us to hypothesize a role of Vanillin in the activation of the cholinergic anti-inflammatory pathway. Furthermore, in presence of mechanical injury, the Vanillin preincubation, wound closure may be reducing the expression and release of IL-6 and TNF-α and upregulation of COX-2 and IL-8. Conclusion. Together, the results of this study highlight the anti-inflammatory and tissue repair ability of Vanillin in IL-1β-primed HGF. Therefore, Vanillin shows a potential therapeutic interest as an inflammatory modulator molecule with novel application in periodontal regeneration and oral health.